VOCABULARY LEARNING STRATEGIES APPLIED BY THE STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM OF BENGKULU UNIVERSITY - Robenna Sihotang; Rudi Afriazi; Imranuddin . (Universitas Bengkulu, 2017)
The aims of this research were to find out vocabulary learning strategies applied by the students of English Education Study Program of Bengkulu University and also the most and the least frequently applied strategies. This research was designed as a descriptive quantitative. The population was 343 students of English Education Study Program of Bengkulu University. The sample of this research was 86 students chosen randomly from the population. The instrument was questionnaire adapted from Schmitt’s Vocabulary Learning Strategies Taxonomy (1997). The result of this study showed that the students applied the six groups of vocabulary learning strategies. However, the mean score of overall strategies indicated that the students applied the strategies in the frequency of “Sometimes”. Moreover, Determination strategy was the most frequently applied by the students, followed by Metacognitive strategy, Cognitive Strategy, Memory strategy, Social (Discovery) strategy, and Social (Consolidation) as the least frequently applied by the students. It can be concluded that the students of English Education Study Program preferred to learn and deal with new word individually to ask people’s helps.